2020
DOI: 10.1088/1742-6596/1483/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fluctuations on the zeros of the energy probability distribution

Abstract: In this communication we explore the possible effects of statistical fluctuations on the use of the Energy Probability Distribution (EPD) zeros to study phase transitions. In the EPD zeros technique one has to find the roots of a polynomial whose coefficients are given by the EPD - a histogram of energy values obtained in a Monte Carlo simulation, for example. Phase transitions are signalized by the presence of a zero that approaches the point (1,0) in the complex plane. Once the EPD estimations are usually su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Iter (Normalized to 1) the zero closest to the point (1, 0). With that said, in a previous study [14], it was observed that the dominant zero is stable to random perturbations in the polynomial coefficients, i.e., applying a perturbation in the EPD following the equation,…”
Section: Solving the Convergence Issuementioning
confidence: 88%
“…Iter (Normalized to 1) the zero closest to the point (1, 0). With that said, in a previous study [14], it was observed that the dominant zero is stable to random perturbations in the polynomial coefficients, i.e., applying a perturbation in the EPD following the equation,…”
Section: Solving the Convergence Issuementioning
confidence: 88%